A Discriminative Syntactic Word Order Model for Machine Translation - Chang, Pi-Chuan; Toutanova, Kristina (Association for Computational Linguistics, 2007)
We present a global discriminative statistical word order model for machine translation. Our model combines syntactic movement and surface movement information, and is discriminatively trained to choose among word orders. We show that combining discriminative training with features to detect these two different kinds of movement phenomena leads to substantial improvements in word ordering performance over strong baselines. Integrating this word order model in a baseline MT system results in a 2.4 points improvement in BLEU for English to Japanese translation.